Sikap Percaya Diri dalam Bentuk Self-love di Kalangan Brand Ambassador UNIBI - Putri, Shinta Hartini; Agistiyani, Aulia; Ulfa, Neng; Lathifah, Nisa (Universitas Informatika dan Bisnis Indonesia, 2024)
In this era, it cannot be denied that there are still many Generation Zs who are lacking in self-confidence. A public speaker or an individual who can communicate in front of an audience is believed to have high self-confidence. An individual who has self-confidence will think that he is a positive individual and has the potential to contribute as well as be able to cooperate with others in various segments of life. Increasing self-confidence can be implemented by applying self-love. Self-confidence and self-love are often found in public figures such as influencers, brand ambassadors, artists, and athletes. UNIBI brand ambassador as one of the icons at UNIBI has a dominant presence and aura. This study aims to provide an overview of the implementation of self-confidence and self-love among UNIBI Brand Ambassadors as input and evaluation material for practicing good self-confidence and self-love among teenagers and the general public. This study uses descriptive qualitative research methods to achieve these objectives, with primary data collection techniques through interviews, while secondary data uses literature studies of books, journals, and internet sources. UNIBI Brand Ambassadors view self-confidence and self-love as an essential thing. Self-love is instilled in each member, although high and good self-confidence is not yet fully implemented or integrated